PENERAPAN SISTEM KOMBINASI ESP-GL UNTUK MENCAPAI KINERJA PRODUKSI OPTIMAL - Kristoper Ginting, Hanafi
As production rate decreases and becomes uneconomically produced naturally, artificial lift is applied to proceed production in an economic manner and environmentally friendly. The selection of artificial lift must be thoroughly analyzed based on specific well conditions which yields the one ultimate artificial lift that will perform best and give the most economic operating condition. Yet, some artificial lifts require high cost for both its capital and operational expenditures. Production optimization must be periodically evaluated to ensure that the optimum condition is achieved. One of which is using combined artificial lift system. Nodal analysis is still used to design both regular and combined system by taking the nodal point at pump discharge of ESP in combined system design. Ensuring the most optimum design is achieved will lead to production performance increment. Combined artificial lift application can overcome limitations of single artificial lift because it has wider operating condition. Higher flowrate can be achieved by using the same ESP due to gas lift effect compared to single system. Gas lift reduces required power and pump stages of ESP. Combined system also improves operating condition in terms of production rates and profit. In addition, production downtime reduction can be achieved because when primary system fails, secondary system can proceed production until primary system gets back to operation and will surely lessen revenue loss decrement. This strategy will be more applicable if there are wells producing gas thus we need no cost to buy gas for gas lift. Combined system, with all of its potentials, has a good prospect to be applied to enhance the production compared to regular system. It can be the best solution to optimize production using the existing technologies before considering EOR. This strategy has never been applied in Indonesia, but there are some cases where combined artificial lift application is proved to be a big success, such as in Xianjin, Balcon, and Tello fields.